Research of the stock price overreaction and investor overconfidence issues - Raharja, Bayu; Suhaeli, Dahli; Mranani, Muji (Business, Management and Economics Engineering, 2017)
This research examines the existing of investor overconfidence in the capital market and the phenomena of stock prices reversal in the future due to the existing of this behavior. It has a different approach to test the existing of investor overconfidence by introducing firm’s growth as the information which has triggered many investors to behave overconfidently. By using multiple regression analysis, the results of this research confirmed our conducted hypothesis, investor tends to behave overconfident to firms which have higher growth. It proofed by the positive relation between firms’ growth and trading volume. Afterward, this research also found that higher growth firms tend to have declining on its performance in the future. The negative relation between firms’ growth and longterm performance means that the stock’s price reversal caused by the existing of investor overconfidence.